Antihyperglycemic Effect of Polyherbal Tea From Moringa oleifera, Cymbopogon citratus, and Stevia rebaudiana Leaves in Alloxan and HFD-Induced Mice (Mus musculus) - Barukh Saro Talenta Zebua; Jekson Martiar Siahaan; Alex M. T. LumbanRaja; Suryati Sinurat; Salomo Garda Utama Simanjuntak (Universitas Methodist Indonesia, 2024)
Diabetes Mellitus (DM) is a disease with metabolic disorders characterized by chronichyperglycemia and disorders of carbohydrate, fat, and protein metabolism due to insulinsecretion disorders. In general, DM patients require pharmacotherapy such as injectedinsulin or oral antidiabetic drugs. Pharmacological treatment is relatively expensive andneeds to consider its efficacy and safety. Therefore, this study explores natural sources suchas medicinal plants. The aim of this study was to determine the antihyperglycemic effect of acombination of boiled moringa leaves, lemongrass leaves and stevia leaves on mice (Musmusculus) induced by alloxan. In this study, 25 mice were divided into 5 groups. The micewill undergo adaptation for 7 days and then given HFD for 30 days. After 30 days, the micewill be given alloxan 170 mg/kgBW for 3 days to induce DM. After DM was successfullyinduced in mice, polyherbal tea combination of moringa leaves, lemongrass leaves and stevialeaves was made and given, then continued with evaluation blood glucose, blood glucosepercentage, body weight, body weight percentage, index lee and liver organ index. The groupgiven herbal tea combination of moringa leaves (Moringa oleifera), lemongrass leaves(Cymbopogon citratus) and stevia leaves (Stevia rebaudiana) with a concentration of 3.6mg/mL showed a better decrease in KGD and %KGD compared to other treatment groups.The decrease in BB, %BB and lee index was better in the group given a combination ofMoringa leaves (Moringa oleifera), Lemongrass leaves (Cymbopogon citratus) and Stevialeaves (Stevia rebaudiana) with a concentration of 7.2 mg/mL. The decrease in the liverorgan index was also better seen in the group given a combination of Moringa leaves(Moringa oleifera), Lemongrass leaves (Cymbopogon citratus) and Stevia leaves (Steviarebaudiana) with a concentration of 7.2 mg/mL. The group given herbal tea combination ofMoringa leaves (Moringa oleifera), Lemongrass leaves (Cymbopogon citratus) and Stevialeaves (Stevia rebaudiana) with a concentration of 3.6 mg/mL reduced BG and BGpercentage, while the group given herbal tea combination of Moringa leaves (Moringaoleifera), Lemongrass leaves (Cymbopogon citratus) and Stevia leaves (Stevia rebaudiana)with a concentration of 7.2 mg/mL reduced BW, BW percentage, Lee index, and hait organindex.